Study of duration of gestation in 500 patients with spontaneous onset of labor - Pandya, Munjal J.; Kotdawala, Parul J.; M. Pandya, Janki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: There have been variations in the length of gestation depending upon the ethnicity of the patient. Methods: We studied 500 patients with spontaneous onset of labor for their duration of pregnancy from First day of Last Menstrual Period (FLMP). Results: The average gestational age was 275 days, 5 days earlier than the Expected date of delivery (EDD). 70% of pregnancies ended before EDD, 4.8% on the day of EDD and 25.2% ended after EDD. 35.80% patients completed 39 weeks, 24% completed 40 weeks, 23.20% completed 38 weeks, 11% completed 37 weeks and only 6% completed 41 weeks. Average gestational age was 39.31 weeks for male baby and 39.36 weeks for female baby. Sex ratio derived was 915.7 females per 1000 males. Average birth weight was 2.705 kg. Conclusions: The implication of this study is that the length of human gestation does vary according to geographic location. This may be due to genetic influences, weather conditions, food habits or some unknown factor. The clinical significance is the decision to consider a term pregnancy and a post-term pregnancy. A majority of the parturient women went in to spontaneous labour at 39 completed weeks, 5 days earlier than ‘Expected date of delivery’ calculated by Naegele’s formula. This possibility should be kept in mind when maturity assessments are made with a view to intervene in the labour process to minimize perinatal complications.